Resveratrol inhibits matrix metalloproteinase-9 transcription in U937 cells - Li Yi-Tang; Shen Fang; Liu Bai-He; Cheng Gui-Fang (Acta Pharmacologica Sinica; Vol 24, No 11 (November 2003): Acta Pharmacologica Sinica, 2016)
AIM: To examine the inhibitory effect of resveratrol on matrix metalloroteinase-9 (MMP-9) and explore its mechanism. METHODS: MMP-9 activity was analyzed by gelatin zymography; MMP-9 protein was detected by Western blot; MMP-9 mRNA expression was investigated by RT-PCR. Activation of activator protein -1 (AP-1) was measured by electrophoretic mobility shift assay (EMSA). RESULTS: MMP-9 activity in U937 cells increased significantly after exposed to PMA at 10 nmol/L for 24 h without FCS (P